Effect of miR‑29a‑3p on renal interstitial fibrosis in diabetic kidney disease through FOXP1‑mediated TGF‑β1/Smad3 signaling pathway - Juntai Zhang; Yan Qin; Jie Liu; Jie Ding; Mengying Xu; Li Yang; Yuanxin Zheng; Chin Kai Ling; Xi Zhang (Springer Nature, 2025)
Renal interstitial fibrosis (RIF) is a major manifestation of diabetic kidney disease (DKD). This study aimed to elucidate the specific mechanism by which miR-29a-3p affects RIF in DKD through Forkhead box protein 1 (FOXP1)-mediated TGF-β1/Smad3 and to provide novel ideas and therapeutic targets for RIF. Cell and animal models were constructed, and CCK-8, flow cytometry, Western blotting, immunofluorescence, RT‒qPCR, Mas- son’s trichrome staining, hematoxylin–eosin (HE) and periodic acid–Schiff (PAS) staining, Sirius red staining, and immunohistochemistry were used to detect the related indicators of RIF in DKD. The interaction between miR-29a-3p and FOXP1 was confirmed using a dual-luciferase assay. These findings suggested that miR-29a-3p can act on renal interstitial fibrosis cells in DKD through the TGF-β1/Smad3 signaling pathway mediated by FOXP1. The overexpression of miR-29a-3p inhibited the expression of fibrin-associated proteins in renal tissue, contracted the mesangial matrix and decreased the accumulation of renal fibrils to ultimately alleviate RIF in DKD. This study is the first to propose the specific molecular mechanism of miR-29a-3p in renal interstitial cells in DKD, which provides novel targets and strategies for the clinical treatment of RIF-related DKD.